ITERATIVE SCHEME FOR FIXED POINT PROBLEM OF ASYMPTOTICALLY NONEXPANSIVE SEMIGROUPS AND SPLIT EQUILIBRIUM PROBLEM IN HILBERT SPACES - Inchan, I. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2020)
The main objective of this work is to modify the sequence $\{x_{n}\}$ of the explicit projection algorithm of asymptotically nonexpansive semigroups. We prove the strong convergence theorem of a sequence $\{x_{n}\}$ to the common fixed point of asymptotically nonexpansive semigroups and the solutions of split equilibrium problems. Our main results extended and improved the results of Pei Zhou and Gou-Jie Zhao [17] and many authors.